Socialization and Education on the Utilization of Binara Herb (Artemisia vulgaris L.) as a Herbal Anti-Aging Cosmetic Ingredient - Romauli Anna Marbun; Ratih Anggraeni; Yanna Rotua Sihombing; Novidawati Boru Situmorang; Cucu Arum Dwi Cahya (JURNAL PENGMAS KESTRA (JPK), 2026)
Background: Premature aging is a common skin health problem caused by exposure to ultraviolet radiation, pollution, and free radicals. Antioxidants play an important role in preventing skin damage by neutralizing free radicals that contribute to premature aging. Binara herb (Artemisia vulgaris  L.) is known to contain flavonoids and other bioactive compounds with strong antioxidant activity. Previous studies have shown that the ethanolic extract of binara herb formulated as a Nanocream exhibits high antioxidant activity, good physical stability, and is safe for topical application. However, information regarding the potential of binara herb as a herbal anti-aging candidate remains limited among the public and students. Objective: his community service activity aimed to provide socialization and education regarding the utilization of Nanocream containing binara herb extract as a safe and innovative natural-based anti-aging product candidate. Methods: The activity was conducted through an online educational program involving students of the Pharmacy Study Program at the Medistra Institute of Health, Lubuk Pakam. Participants’ knowledge was evaluated using pre-test and post-test questionnaires. Results: The educational materials covered the antioxidant benefits of binara herb, the concept of Nanocream, findings from anti-aging activity studies, product safety, and the potential development of herbal cosmetic products based on nanotechnology. The evaluation results showed that more than 90% of participants understood the benefits of binara herb as a natural antioxidant source and recognized the potential of Nanocream as a future anti-aging formulation. The success indicator of the activity was achieved, with more than 80% of participants obtaining post-test scores above 75. Conclusion: The educational and socialization program successfully improved students’ knowledge regarding the utilization of Nanocream containing binara herb extract as a natural-based anti-aging candidate. The students also demonstrated interest in conducting further research related to the development of herbal cosmetics and nanotechnology applications in the pharmaceutical field.